Iron-catalyzed tandem reaction of C–Se bond coupling/selenosulfonation of indols with benzeneselenols. Issue 45 (20th July 2020) - Guan, Senling; Chen, Yue; Wu, Hongjie; Xu, Runsheng
Abstract : Iron-catalyzed tandem reaction of C–Se bond coupling/selenosulfonation. Abstract : An iron-catalyzed tandem reaction of C–Se bond coupling/selenosulfonation was developed. Starting from sample indols and benzeneselenols versatile biologically active 2-benzeneselenonyl-1 H -indoles derivatives were efficiently synthesized. The reaction mechanism was studied by the deuterium isotope study and in situ ESI-MS experiments. This protocol features mild reaction conditions, wider substrate scope and provides an economical approach toward C(sp 2 )–Se bond formation.